2019
DOI: 10.1111/pce.13694
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association study reveals new genes involved in leaf trichome formation in polyploid oilseed rape (Brassica napus L.)

Abstract: Leaf trichomes protect against various biotic and abiotic stresses in plants. However, there is little knowledge about this trait in oilseed rape (Brassica napus). Here, we demonstrated that hairy leaves were less attractive to Plutella xylostella larvae than glabrous leaves. We established a core germplasm collection with 290 accessions for a genome‐wide association study (GWAS) of the leaf trichome trait in oilseed rape. We compared the transcriptomes of the shoot apical meristem (SAM) between hairy‐ and gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 76 publications
0
34
0
Order By: Relevance
“…To reveal natural variation of genomic sequences of GATA genes in B. napus, SNPs in the coding regions of GATA genes were determined in a worldwide collection of B. napus germplasm of 300 accessions in light of the genome re-sequencing data of our previous studies [26,27]. Highquality SNPs with MAF larger than 5% and missing rate less than 50% were used for the further analysis.…”
Section: Snp Distribution Of Gatas In a Core Collection Of B Napusmentioning
confidence: 99%
See 1 more Smart Citation
“…To reveal natural variation of genomic sequences of GATA genes in B. napus, SNPs in the coding regions of GATA genes were determined in a worldwide collection of B. napus germplasm of 300 accessions in light of the genome re-sequencing data of our previous studies [26,27]. Highquality SNPs with MAF larger than 5% and missing rate less than 50% were used for the further analysis.…”
Section: Snp Distribution Of Gatas In a Core Collection Of B Napusmentioning
confidence: 99%
“…To date, the genomes of Darmor-bzh (winter ecotype), Tapitor (winter ecotype), Zhongshuang 11 were successfully sequenced and assembled [23][24][25]. Recently, we re-sequenced 991 accessions from the global rapeseed germplasm and established a worldwide core collection [26,27]. In this study, 96 GATA genes were identified and characterized in the genome of B. napus.…”
Section: Introductionmentioning
confidence: 99%
“…The polymorphism of BnSnRK genes was determined using our previous resequencing data of a core germplasm resource containing 300 accessions [29,30]. The SNPs with MAF more than 5% in BnSnRK genes were selected out (Table S9).…”
Section: Snps Analysis Of Bnsnrks In a Core Germplasm Of Bnapusmentioning
confidence: 99%
“…The SNPs in the coding regions of BnSnRK genes were extracted from the total SNPs of 300 B.napus accessions, which were determined by the genome re-sequencing in our previous studies [29,30]. High-quality SNPs with MAF greater than 5% and missing rate less than 50% were used for further analysis.…”
Section: Snp Distribution Analysis Of Bnsnrks In Bnapus Accessionsmentioning
confidence: 99%
“…Therefore, in BnaSNPDB, the analyses were based on SNP variations. FLOWERING LOCUS C ( BnaA10g22080D ) [4] and SWEET4 ( BnaC07g24860D ) [20] were used as examples to show the associations between allelic SNP variations in genetic populations and agronomic traits, such as flowering time and leaf trichome, respectively, and to demonstrate the efficiency of the tools ( Fig. 2 A; Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%